Science for All? Practical Recommendations on Reaching Underserved Audiences - Humm, Christian; Schrögel, Philipp (Frontiers in Communication, 2020)
In a world decisively influenced by scientific developments science communication grows ever more important to enable informed decision making and participation of citizens in society and political discourse. However, science communication, being it public talks or participatory projects, often reaches only certain parts of society. While this problem is increasingly recognized, only some empirical results and practical recommendations on success-factors for promoting diversity and inclusiveness in science communication exist so far. If at all, many projects and reports focus on very specific areas with only a few aggregated and overarching best practices and guidelines. This article contributes to filling this gap and presents a set of practical recommendations on reaching and engaging underserved audiences of science communication activities. The proposed guidelines have been developed from the experiences and empirical evidence from the research and practice project “Science for All” in Germany, and are based on a review of existing guidelines and recommendations. They are corroborated by interviews with practitioners, scientists, and underrepresented groups. The seven recommendations include listening to underserved audiences, reducing the distance, illustrating the relevance of science for daily life, going where the people are, cooperating with stakeholders and multipliers, as well as the problem of too much openness and one-time activities. The guidelines are primarily addressed at practitioners in the field of science communication and meant to encourage and support a first step towards more diverse and inclusive science communication. However, they are limited wherever the roots of exclusion lay at the societal and political level and are open for discussion. While inclusive science communication alone cannot fix discrimination and inequality in society, a continuous self-reflection and improvement of the communication of science organizations, including the improvement of inclusion and diversity within the organization themselves, is an important contribution to a more equitable society.